Bergamot Polyphenols: Promising Agents for Health and Wellness - Gruca, Dariusz; Wais, Marcin; Zając, Marlena; Zalewski, Paweł; Wróblewski, Wiktor; Raabe, Adam (Journal of Education, Health and Sport, 2024)
Introduction and purpose: Citrus bergamia, commonly known as bergamot, is a unique plant native to the Calabria region in Italy, prized for its fragrant fruits and versatile applications. Historically utilized for extracting essential oil, bergamot has garnered attention for its therapeutic properties, particularly its Bergamot-derived Polyphenolic Fraction (BPF), which exhibits lipid-lowering, antioxidant, and anti-inflammatory effects. This paper aims to provide a comprehensive summary of existing research on the therapeutic potential of BPF in humans. Brief description of the state of knowledge: BPF has shown promise in supporting wound healing, alleviating neuropathic pain, and exhibiting antimicrobial properties. Research highlights BPF’s role in modulating lipid metabolism, particularly in reducing LDL cholesterol and triglycerides while increasing HDL cholesterol levels. Additionally, BPF demonstrates anti-inflammatory effects, accelerating the recovery process in conditions such as non-alcoholic steatohepatitis (NASH) and potentially influencing pathways involved in cancer cell proliferation and apoptosis. Further studies explore BPF’s impact on bone metabolism, erectile dysfunction, and its potential in dermatological applications, particularly in counteracting photoaging. Conclusions: While existing studies underscore the promising therapeutic effects of BPF in various medical domains, further research is warranted to establish its efficacy and safety for broader clinical use. Continued investigation on a larger scale holds the potential to develop BPF as a valuable physiotherapeutic strategy across diverse medical fields.